Historical analysis of biomedical sciences teaching and their integration in Dentistry - Miriela Betancourt Valladares; Rolando Miguel Bermejo Correa; Mercedes Caridad García González; Kenia Betancourt Gamboa (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
The integration of scientific contents is a global trend in its teaching and it is relevant due to its social impact for problem solving. The paper analyses the historical evolution of the teaching learning of biomedical sciences, emphasizing on its contents integration from Physiology, in the Dentistry degree course. Among the theoretical methods, the logical-historical; the synthetic -analytic and the inductive-deductive were used; and from the empirical level, the documents analysis was carried out. Critical opinion and collective building workshops allowed to define the assumed indicators. A characterization of four stages from 1992 up to date is offered and tendencies of the teaching learning process of biomedical sciences in relation to their integration. Modifications in favor to contents integration were found, however there are limitations from the theoretical, methodological and practical points of view to achieve it.